Strategic Analysis of Embedded Digital Donation Mujamma Infrastructure In Indonesia’s Digital Banking And Super App Ecosystem: A Case Study Bank Nano and Mytelkomsel - Ammar Alfarisy (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The rapid development of the digital banking industry, particularly the implementation of mobile banking as the primary banking channel, has transformed customers' daily financial transaction behavior. Almost all daily transactions, from bill payments and hotel or flight reservations to the purchase of goods, can be conducted through customers' mobile banking applications. On the other hand, social or philanthropic institutions face difficulties in raising funds for social programs, even through digital fundraising or crowdfunding systems. Currently, integration between digital fundraising through institutional websites and the Islamic social financial system, represented by mobile banking applications, remains limited, creating a significant gap between the rapid growth of mobile banking platforms and the slow pace of transactions through social institution fundraising applications. The study will examine how Mujamma, which is implemented as a digital donation infrastructure or platform provider, can be integrated with mobile banking ecosystems to implement a sharia-compliant donation scheme. By integrating such a scheme, the system will aim at reaching out millions of clients at ex post prohibitive costs, increasing the confidence of the user base and improving on the favorability of social program donations. At the same time, the model assumes the creation of the additional fee-based sources of revenues of the banking institution. Using a qualitative case study approach to examine the implementation at Bank Nano and MyTelkomsel, supported by interviews and analyses of PESTEL, STP, SWOT, and TOWS, the findings show that Mujamma's white-label, modular, and storytelling-based model provides an emotionally memorable donation experience for customers, thereby increasing donation transactions. However, the integration process with mobile banking requires intensive interaction and dependence on the Bank's execution, so this study recommends a selective growth strategy that focuses on automating integration from social institutions independently and selecting Banks that are ready with a digital integration system and have the need to make donations as one of the main features of their mobile banking. The characteristics of banks like this include Islamic banks with a relatively strong digital strategy.